Angular estimations of certain integral operators - Nak Eun Cho; In Hwa Kim; Ji A Kim (International Journal of Mathematics and Mathematical Sciences)
The object of the present paper is to derive some argument properties of certain integral operators. Our results contain some interesting corollaries as the special cases.